Thickness of the surface layer of porous silicon - Yurov, V.M. (Recent Contributions to Physics, 2020)
Semiconductor materials with nanoscale structural elements are promising materials for modern electronics. Due to this structure, porous silicon exhibits unique physicochemical properties that single crystal silicon does not possess. The literature describes two methods for producing layers of porous silicon. This is chemical staining etching without applying an external electric field and anodic electrochemical etching of a silicon wafer in an external electric field. In this paper, we discuss the problem of the surface layer of porous silicon. A layer of thickness h = d is called a d(I) layer, and a layer at h≈10d is called a d(II) layer of atomically smooth silicon. At h≈10d, the dimensional dependence of the physical properties of the material begins to appear, and such a structure is called a nanostructure. At h = d, a phase transition occurs in the surface layer. It is accompanied by sharp changes in physical properties, for example, the direct Hall-Petch effect is reversed. The analysis of the work describing the properties of porous silicon, single-crystal silicon is carried out. It has been shown that, starting from 80% porosity, silicon, by its properties of the d(II)Si layer, extends beyond the Glater nanostructure. For most pure metals, the thickness of the surface layer d(I) does not exceed 3 nm (for d(II) 30 nm).